Survival estimates of wild and captive-bred released Puaiohi, an endangered Hawaiian thrush. (5th November 2014) - VanderWerf, Eric A.; Crampton, Lisa H.; Diegmann, Julia S.; Atkinson, Carter T.; Leonard, David L.
Abstract: Estimating and monitoring adult and juvenile survival are vital to understanding population status, informing recovery planning for endangered species, and quantifying the success of management. We used mark–recapture models to estimate apparent annual survival of the Puaiohi ( Myadestes palmeri ), an endangered thrush endemic to the Hawaiian island of Kauai, from 2005 to 2011. Our sample included 87 wild birds and 123 captive-bred birds that were released at various ages. Survival was higher for wild adult males (0.71 ± 0.09) than for wild adult females (0.46 ± 0.12). Survival of wild juveniles (0.23 ± 0.06) was lower than that of wild adults of both sexes, indicating that recruitment may limit population growth. Captive-bred birds released when <1 yr old had survival (0.26 ± 0.21) comparable with that of wild juveniles, but captive-bred birds released at 1–3 yr old had very low survival (0.05 ± 0.06). Only 8 of 123 (7%) captive birds were seen again after release. Two wild birds resighted five years after marking are the oldest known individuals, being at least six years of age. Malarial infection did not affect survival of wild Puaiohi, unlike many Hawaiian forest birds. The difference between adult male and adult female survival is consistent with rat ( Rattus spp.) predation of females on the nest as a major source of mortality. As such, attempting to reduce nest predation by controlling rats may be the best available management option. Releasing captive-bred birds has had little effect on the wild population in recent years.